2003
DOI: 10.1073/pnas.1834478100
|View full text |Cite
|
Sign up to set email alerts
|

A dually active anthrax vaccine that confers protection against both bacilli and toxins

Abstract: Systemic anthrax is caused by unimpeded bacillar replication and toxin secretion. We developed a dually active anthrax vaccine (DAAV) that confers simultaneous protection against both bacilli and toxins. DAAV was constructed by conjugating capsular poly-␥-D-glutamic acid (PGA) to protective antigen (PA), converting the weakly immunogenic PGA to a potent immunogen, and synergistically enhancing the humoral response to PA. PGA-specific antibodies bound to encapsulated bacilli and promoted the killing of bacilli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
113
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 27 publications
(29 reference statements)
5
113
0
Order By: Relevance
“…As shown by others (8,9), preliminary studies found little or no Ab response after immunization with ␥DPGA alone. As a consequence, we attempted immunization of BALB͞c mice with B. licheniformis ␥DPGA in combination with CD40 agonist mAb.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…As shown by others (8,9), preliminary studies found little or no Ab response after immunization with ␥DPGA alone. As a consequence, we attempted immunization of BALB͞c mice with B. licheniformis ␥DPGA in combination with CD40 agonist mAb.…”
Section: Resultsmentioning
confidence: 62%
“…The extent to which a toxin-based immunity alone can protect against the potential large inoculum that might occur in a bioterrorism attack is not known. One approach to an improved vaccine formulation is a conjugate vaccine that targets both the antiphagocytic capsule and the toxin (8,9). Our results provide strong proof of concept for targeting ␥DPGA in a vaccine formulation and suggest efficacy of passive immunization in individuals who have not been immunized (21).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Given the important role of the capsule in virulence, several recent studies have used the capsule of B. anthracis as a potential target for vaccine and neutralizing mAb development (14)(15)(16)(17)(18)(19)(20). These studies demonstrated that both active and passive vaccination targeting the B. anthracis capsule protected animals against experimental infection, suggesting that methods to increase the phagocytosis of encapsulated B. anthracis bacilli may be valuable in the treatment of anthrax.…”
mentioning
confidence: 99%